2014
DOI: 10.3109/13651501.2014.957704
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder in children is found to be related to the occurrence of ADHD in siblings and the male gender, but not to birth order, when compared to healthy controls

Abstract: Compared to controls, the occurrence of ADHD was found to be related to the male gender and to the occurrence of ADHD-related symptoms in siblings (odds ratio: 13.50). Birth order and MR were not associated with the occurrence of ADHD and ADHD-related symptoms. ADHD- related symptoms increased if a further sibling also suffered from ADHD. Conclusions. Among a sample of Iranian children suffering from ADHD, the ADHD and ADHD-related symptoms in childhood were found to be related to the male gender and to the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Similarly, no difference in ADHD prevalence was found between urban and rural samples. In contrast to Keshavarzi et al (2014) and Berger and Felsenthal-Berger (2009), a higher prevalence was recorded in first-born children, which is in agreement with another study (Masana et al, 2014). However, parental age and first/degree family history of mental disorder were not related to ADHD diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, no difference in ADHD prevalence was found between urban and rural samples. In contrast to Keshavarzi et al (2014) and Berger and Felsenthal-Berger (2009), a higher prevalence was recorded in first-born children, which is in agreement with another study (Masana et al, 2014). However, parental age and first/degree family history of mental disorder were not related to ADHD diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Chang et al (2014) also found that teenage mothers (<20 years) were 78% more likely to have a child with ADHD. However, some researchers suggest that ADHD could be related to the occurrence of the disorder in siblings, but not to birth order (Keshavarzi, Bajoghli, Mohamadi, Holsboer-Trachsler, & Brand, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to one analysis that measured the worldwide burden of mental and substance abuse disorders in terms of disability‐adjusted life years, boys aged 10 years and under were found to bear a greater burden than girls, whereas women at age 15 years and older bear a greater burden than men (Whiteford et al, ). The increased burden for boys during childhood likely is due to the higher incidence of childhood behavioral disorders among boys (e.g., autism‐spectrum disorders, attention deficit‐hyperactivity disorder; Whiteford et al, ; Keshavarzi et al, ; Christensen et al, ). The increased burden in women likely results from greater prevalence, progression, and/or severity of conditions such as anxiety and mood disorders, schizophrenia, and Alzheimer's disease (Launer et al, ; Pigott, ; Kessler et al, ; Gillies and McArthur, ).…”
Section: Conclusion and Implications For Future Researchmentioning
confidence: 99%
“…Although the nature and magnitude of these differences have been subject to debate (see, e.g., Joel et al, ; McCarthy and Konkle, ), compared few studies have been conducted on this subject compared to similar topics in neuroendocrinology (e.g., effects of estrogens on cognition in females). This issue is particularly important for mental health, given the existence of sex differences in the prevalence and symptomatology of disorders such as autism, depression, substance abuse, and Alzheimer's disease (Launer et al, ; Pigott, ; Kessler et al, ; Lejuez et al, ; Gillies and McArthur, ; Whiteford et al, ; Keshavarzi et al, ; Christensen et al, ). Thus, considerably more research at multiple levels of analysis is needed to fully understand the existence and neurobiological origins of sex differences in cognition.…”
mentioning
confidence: 99%
“…25,26 Siblings of children with ADHD or ASD are also at higher risk for other emotional, behavioral, and psychosocial challenges. 27,28 Unexpectedly, we reported that having more than one child with a chronic condition predicted a lower likelihood of having an inpatient stay. This may indicate these children had less severe illness associated with their conditions.…”
Section: Discussionmentioning
confidence: 67%